circZNF91 Promotes the Malignant Phenotype of Chronic Lymphocytic Leukemia Cells by Targeting the miR-1283/WEE1 Axis - Shaoting Li (BioMed Research International, 2022)
Background. Circular RNAs (circRNAs) are frequently dysregulated in cancers and are implicated in tumorigenesis and tumor progression. In this study, we investigated the role of circZNF91 in regulating the malignant phenotype of chronic lymphocytic leukemia (CLL) cells and the underlying molecular mechanism. Material/Methods. The expression of circZNF91 was determined by reverse transcription-quantitative polymerase chain reaction (RT-qPCR). The binding sequences between circZNF91/miR-1283 and miR-1283/WEE1 were predicted by the bioinformatic database. The functional interactions were confirmed by the dual-luciferase reporter, RT-qPCR, and Western blot assays. The functional roles of the circZNF91/miR-1283/WEE1 axis in CLL progression were examined by cell proliferation, apoptosis, and EdU incorporation assays. Results. circZNF91 was upregulated in CLL samples. Silencing circZNF91 attenuated CLL cell proliferation and induced apoptosis and cell cycle arrest. circZNF91 could sponge miR-1283 to suppress its activity, which in turn upregulated WEE1 expression. Silencing circ-TTBK2 reduced WEE1 expression, while the inhibitor of miR-1283 enhanced WEE1 expression. The miR-1283/WEE1 axis mediated the effects of circZNF91 on cell proliferation and apoptosis, as well as induced cell cycle regulation. Conclusions. The circZNF91/miR-1283/WEE1 axis is engaged in the pathological phenotypes of CLL cells, which could serve as potential targets for future therapy development.